Intertemporal poverty measurement: tradeoffs and policy options - Porter, C; Quinn, N (CSAE (University of Oxford), 2008)
This paper makes three contributions to the literature on intertemporal poverty measurement, in particular the aggregation of a measure of wellbeing over time and across people. Firstly we conduct an exhaustive analysis of properties of intertemporal poverty measures, identifying relationships between the functional form and properties of ITPMs and identifying the tradeoffs and compatibilities that exist between the properties. We link this to the normative choices a poverty analyst must make when measuring intertemporal poverty. We also determine a ‘recipe’ which may be used to construct poverty measures with properties desired by the poverty analyst. Second, we apply the recipe to construct a new family of intertemporal poverty measures with the desired property of increasing compensation, a property that has thus far not been discussed in the literature. Third, we calculate measures from the new family and compare them to other measures recently proposed in the literature, to evaluate poverty in rural Ethiopia in the period 1994 - 2004.